A LOCALIZED OUTBREAK OF CHOLERA DUE TO VIBRIO CHOLERAE O1, OGAWA RESISTANT TO TETRACYCLINES: Outbreak of Cholera Resistant to Tetracyclines - Ahmed, Shahid; Afzal, Raja Kamran; Mian, Umar Arif (Pakistan Armed Forces Medical Journal, 2015)
Objective: To study the clinical and laboratory parameters of a localized Cholera outbreak and determine the sensitivity pattern of the subtype involved. Study Design: A descriptive study. Place and Duration of Study: Combined Military Hospital, Lahore. Duration of Study: Two weeks. Patients and Methods: The study is about a localized outbreak of cholera in a group of soldiers, who consumed water from a single contaminated source of water. We are presenting here an account of the clinical and laboratory parameters of 39 hospitalized cases of cholera, who presented with profuse watery diarrhoea and vomiting. There vital signs, hydration status and systemic examination findings were recorded. Stool samples were sent for routine and microscopic examination and bacteriological culture. Blood samples were taken for complete blood count, serum sodium, potassium, urea and creatinine examination. SPSS 18 was used for statistical analysis of the results. Results: The average age of thirty nine men studied in this outbreak was 24.9 ± 6.9 years. There was no statistically significant difference between confirmed and suspected cholera cases on descriptive analysis of the clinical and laboratory parameters. Majority of patients showed pre-renal azotemia which improved within 48 to 72 hours of hospitalization. Stool cultures isolated Vibrio cholerae O1, subtype Ogawa, which was resistant to tetracyclines, cotrimoxazole and nalidixic acid but sensitive to fluoroquinolones and third generation cephalosporins. The outbreak was controlled when the contaminated water source was sealed and rectified. Conclusion: Multiple drug resistance strains of Vibrio cholera are causing large outbreaks which should be controlled by prevention of the disease and avoiding inappropriate use of antibiotics.